Leishmania infantum pyridoxal kinase evaluated in a recombinant protein and DNA vaccine to protects against visceral leishmaniasis. (August 2020) - Oliveira-da-Silva, João A.; Lage, Daniela P.; Ramos, Fernanda F.; Machado, Amanda S.; Tavares, Grasiele S.V.; Mendonça, Débora V.C.; Pereira, Isabela A.G.; Martins, Vívian T.; Carvalho, Lívia M.; Ludolf, Fernanda; Santos, Thaís T.O.; Reis, Thiago A.R.; et al.
Graphical abstract: Highlights: The pyridoxal kinase (PK) protein was evaluated against visceral leishmaniasis. The protein was administered as a recombinant antigen or DNA vaccine. Mice receiving both immunization schedules developed a Th1-type response. Significant reductions in the organic parasitism were found in these animals. The PK protein was immunogenic in PBMCs from treated patients and healthy subjects. Abstract: Leishmania infantum pyridoxal kinase (PK) protein was characterized after an immunoproteomics screening performed with the sera from patients suffering visceral leishmaniasis (VL). Since it was recognized by sera of mammalian hosts infected by a viscerotropic Leishmania species, PK could emerge as a new vaccine candidate against disease, due to its antigenicity and immunogenicity. In this context, in the present study, the effects of the immunization using PK were evaluated when administered as a DNA plasmid (pDNAA3/PK) or recombinant protein (rPK) plus saponin. The immune response elicited by both vaccination regimens reduced in significant levels the parasite load in spleen, liver, draining lymph nodes and bone marrow, being associated with the development of Th1-type immune response, which was characterized by high levels of IFN-γ, IL-12, GM-CSF, and specific IgG2a antibody, besides low production of IL-4, IL-10, and protein and parasite-specific IgG1 antibodies. CD8 + T cells were more important in the IFN-γ production in the pDNAA3/PK group, while CD4 + T cells contributed more significantly to production of this cytokine in the rPK/Saponin group. In addition, increased IFN-γ secretion, along with low levels of IL-10, were found when PBMCs from VL patients after treatment and healthy individuals were stimulated with the protein. In conclusion, when administered either as a DNA plasmid or recombinant protein plus adjuvant, PK can direct the immune response towards a Th1-type immune profile, protecting mice against L . infantum challenge; therefore, it can be seen as a promising immunogen against human VL.